(untitled) (Environment & Health, 2021)
Background: The growing prevalence of non-communicable diseases (NCD), which cause the high mortality and disability, necessitates the research to prevent them and improves early diagnosis. Currently, the relevance of the NCD prevention is of particular importance because the NCD patients have an increased risk of the severe course of the COVID-19. Taking into account the processes of urbanization, the study of the features of epidemiology of risk factors for the development of the NCD should be conducted separately for urban and rural populations. Objective: We aimed to systematize the risk factors of non-communicable diseases in the urban population of Ukraine. Materials and methods: We used the bibliosemantic method and method of structural and logical analysis. A contextual search was conducted in such databases as the State Statistics Service of Ukraine, the World Health Data Platform, the IHME Global Burden of Disease, as well as in the available publications in the system of PubMed, Cochrane Library. Results: Demographic trends in Ukraine are characterized by a predominance of mortality over birth rate, and since 1990, the population has decreased by 19.2%. Non-communicable diseases are the leading cause of death in the Ukrainians and risk factors that contribute to NCD are common in the population. The increase in mortality is due to both the effect of risk factors and the late diagnosis of the NCD. More than a half of the population aged over 18 years is overweight and obese. In large cities over the past 5 years there has been a sharp increase in the proportion of obese people. Hypodynamia and irrational nutrition are also characteristic features of urban residents. Atmospheric pollution is an additional NCD risk factor. Conclusions: The urban population of Ukraine is characterized by such risk factors of the NCD as population aging, hypokinesia, irrational nutrition, atmospheric pollution, hypodiagnosis of the NCD. All these threats in the combination with a low socio-economic level of the population form a need in more active implementation of the preventive measures.